After the mammoths: The ecological legacy of late Pleistocene megafauna extinctions - Felisa A. Smith; Emma A. Elliott Smith; Carson P. Hedberg; S. Kathleen Lyons; Melissa I. Pardi; Catalina P. Tomé (Cambridge Prisms: Extinction, 2023)
The significant extinctions in Earth history have largely been unpredictable in terms of what species perish and what traits make species susceptible. The extinctions occurring during the late Pleistocene are unusual in this regard, because they were strongly size-selective and targeted exclusively large-bodied animals (i.e., megafauna, >1 ton) and disproportionately, large-bodied herbivores. Because these animals are also at particular risk today, the aftermath of the late Pleistocene extinctions can provide insights into how the loss or decline of contemporary large-bodied animals may influence ecosystems. Here, we review the ecological consequences of the late Pleistocene extinctions on major aspects of the environment, on communities and ecosystems, as well as on the diet, distribution and behavior of surviving mammals. We find the consequences of the loss of megafauna were pervasive and left legacies detectable in all parts of the Earth system. Furthermore, we find that the ecological roles that extinct and modern megafauna play in the Earth system are not replicated by smaller-bodied animals. Our review highlights the important perspectives that paleoecology can provide for modern conservation efforts.